Modeling of measurement errors of general normals teeth and of the indicators sorting - Дербаба, Виталий Анатольевич (Eastern-European Journal of Enterprise Technologies, 2013)
For the choice of the measuring instruments with an acceptable measurement error, the technique, given in the national standard GOST 8.051-81 is used. However, this technique is applicable only to smooth junctions and does not take into account geometrical features of involute teeth of wheels. The objective of the paper is to determine the dependence of the sorting indicators of base tangents of involute teeth on the limiting random error of measurement. The method of simulation statistical modeling, adapted in relation to the assigned task was applied. The modeling was carried out both for the case of zero error of measurement, and for the limiting value of the random error, which is taken as input data. It provides the calculation of the percent of incorrectly accepted and incorrectly rejected pairs of teeth. The statistical modeling was conducted on the basis of the random number generator, built in Microsoft EXCEL. The accepted assumptions concern the choice of the law of normal distribution for deviations of base tangent lengths from the nominal value and uniform law of distribution of random errors of measurement. The dependences of the number of incorrectly accepted and incorrectly rejected pairs of teeth on limiting values of random error of measurement of base tangent length for degrees of accuracy of gearing 4, 5, 6, 7, 8 with various types of junction were obtained. The procedure was used in the educational processes when training bachelors, specialists and masters in mechanical engineering. The technique can be used in drawing up business-plans for decision-making during preparation of engineering production, which is characterized by the stochastic nature